Amphipathic Molecules Endowing Highly Structure Robust and Fast Kinetic Vanadium‐Based Cathode for High‐Performance Zinc‐Ion Batteries. Issue 6 (15th April 2022) - Zhu, Mengyu; Wang, Huibo; Lin, Wang; Chan, Dan; Li, Heng; Wang, Kexuan; Tang, Yu; Hao, Tianwei; Chen, Shi; Malyi, Oleksandr I.; Tang, Yuxin; Zhang, Yanyan
Abstract : Layered vanadium oxides with high theoretical capacity and long cycle life are promising cathode materials to achieve the high energy density of aqueous zinc‐ion batteries (ZIBs). However, the unstable layered structure and slow Zn 2+ diffusion in vanadium oxide during cycling still hinder their practical application. To this end, amphiphilic quaternary ammonium salt cationic surfactant with different chain lengths into V2 O5 ·0.8H2 O (HVO) to modulate the desolvation process of Zn 2+ and layer space of HVO is introduced. Benefitting from the rational design, the assembled Zn//[N(C4 H9 )4 ]0.11 V2 O5 ·0.6H2 O (TBAVO) battery owns a higher capacity (445 mAh g −1 at 0.1 A g −1 ), better rate‐performance, and superior cycling life (e.g., 142 mAh g −1 at 8.0 A g −1 with a capacity retention rate of 91% after 3600 cycles) than that of others due to the reduced desolvation energy barriers, less water molecular insertion, and optimized layer space with the smallest (001) peak variations during cycling. Even at −40 °C, the capacity can reach 125 mAh g −1 at 1.0 A g −1 with almost no capacity decay after 1600 cycles. The strategy offers a new solution to develop high‐performance ZIBs by regulating the desolvation process in cathodes with amphipathic molecules. Abstract : An amphipathic surfactant modified approach to regulate the desolvation energy of zinc ions and layer distance of vanadium‐based cathode for boosting ZIBs performance in terms of rate‐capability and cycling life is introduced. The strategy offers a new solution to develop high‐performance ZIBs by regulating the desolvation process in cathodes with amphipathic molecules.